ACE I/D and ACTN3 R577X genotypes, muscular and cardiovascular fitness in Malay males (Funded work) - XIAO LI; FOONG KIEW OOI; SHING CHENG TAN; BIN ALWI ZILFALIL (International Journal of Pharma and Bio Sciences, 2018)
To date, limited studies have been performed to investigate the frequency of ACE I/D and ACTN3 R577X polymorphisms in Malay population. Moreover, information on the association of these two polymorphisms with muscular performance, aerobic and Wingate anaerobic capacities in Malay physically active males are limited. Hence, the present study was designed to investigate the association of ACE I/D and ACTN3 R577X polymorphisms with muscular performance, aerobic and Wingate anaerobic capacities among Malay young males. Sixty six Malay males (physically active, n=33; physically non-active, n=33) were recruited. Participants’ flexibility, hand grip strength, back and leg strength, standing long jump power, vertical jump power, lung functions, maximum oxygen uptake (VO2max) measured via treadmill running test, Wingate anaerobic capacities were measured. Genotyping of ACE I/D and ACTN3 R577X polymorphisms were performed on genomic DNA of the participants. Among physically active participants, II and ID genotypes of the ACE polymorphism were significantly associated with higher forced vital capacity and VO2max. Additionally, ACE ID genotype was significantly associated with greater back and leg strength and peak power respectively. Physically active participants with ACTN3 RR genotype exhibited significantly higher mean power and peak power as compared to those with XX genotype. These findings imply that ACE II genotype to be associated with greater aerobic capacity. ACE ID genotype were found not only to be associated with greater aerobic capacity, but also with greater muscular strength and anaerobic peak power. In addition, ACTN3 RR genotype seems to be associated with greater anaerobic performance among Malay physically active young males.